How does fiscal decentralization affect aggregate, national, and subnational government size? - Jin, Jing; Zou, Heng-fu (2002)
Beyond conducting the usual regression analysis of the relationship between fiscal decentralization and aggregate government size (national and subnational combined), this paper makes the first attempt to examine how different fiscal decentralization measures affect the sizes of national and subnational (state and local combined) governments. An econometric analysis using panel data from 32 industrial and developing countries, 1980-1994, finds that (1) expenditure decentralization leads to smaller national governments, larger subnational governments, and larger aggregate governments; (2) revenue decentralization increases subnational governments by less than it reduces national governments, hence leads to smaller aggregate governments; and (3) vertical imbalance tends to increase the sizes of subnational, national, and aggregate governments. - Reproduced.
Keywords: Fiscal policy